A current and future outlook on upcoming technologies in remote monitoring of patients with heart failure. (18th November 2020) - Bekfani, Tarek; Fudim, Marat; Cleland, John G.F.; Jorbenadze, Ana; von Haehling, Stephan; Lorber, Avraham; Rothman, Alexander M.K.; Stein, Kenneth; Abraham, William T.; Sievert, Horst; Anker, Stefan D.
Abstract : Heart failure is a major health and economic challenge in both developing and developed countries. Despite advances in pharmacological and device therapies for patients with a reduced left ventricular ejection fraction (LVEF) and heart failure, their quality of life and exercise capacity are often persistently impaired, morbidity and mortality remain high and the health economic and societal costs are considerable. For patients with heart failure and preserved LVEF, diuretic management has an essential role for controlling congestion and symptoms, even if no intervention has convincingly shown to reduce morbidity or mortality. Remote monitoring might improve care delivery and clinical outcomes for patients regardless of LVEF. A great variety of innovative remote monitoring technologies and algorithms are being introduced, including patient self‐managed testing, wearable devices, technologies either integrated into established clinically indicated therapeutic devices, such as pacemakers and defibrillators, or as stand‐alone are in development providing the promise of further improvements in service delivery and clinical outcomes. In this article, we will discuss unmet needs in the management of patients with heart failure, how remote monitoring might contribute to future solutions, and provide an overview of current and novel remote monitoring technologies. Abstract : Different remote monitoring options (wearables, non‐invasive devices like ReDS™, integrated algorithms in implanted cardiac devices like HeartLogic™). The resulting data will be transferred to medical centres and will be reviewed frequently from medical personnel (physicians, trained nurses, etc.). Accordingly, decisions should be made to modify the medical therapy or to organize an emergent admission of the patients. Alternatively, no action could be required assuring a stable condition of heart failure (HF) patients.